How to Enhance Customer Loyalty to Retail Stores via Retail Service Quality Practices? A Moderated Mediated Mechanism - Achchuthan, S.; Shankar, A.; Manish, D.; Konalingam, K. (Taylor & Francis Group, 2022)
This study proposes and empirically investigates a moderated mediation mechanism to enhance consumer loyalty via retail service quality (RSQ) practices. The results revealed that the impact of physical aspect, reliability, personal interaction, and policy on customer loyalty is significantly mediated by the affective commitment to the retailers. Further, the retailer’s corporate image enhanced the indirect effects of reliability, personal interaction and retailing policy on customer loyalty. By investigating how the interplay of RSQ dimensions, affective commitment and corporate image enriches retail service qual-ity, this study contributes to the retailing literature
Keywords: Retail Service Quality (RSQ); Affective commitment; Corporate image; Moderated mediation; Customer loyalty